DYNAMICS OF RACISM AGAINST ASIAN ETHNICITY IN THE UNITED STATES AND THE RESISTANCE IN THE DIGITAL AGE - Panjaitan, Ocxynuel; Sagena, Uni W. (International Journal of Social Science, 2025)
Racism has been a strong part of history in the United States since the 19th century. Racism has increased again during the Covid-19 pandemic targeting Asian-Americans, due to a long history and social media tweets from government institutions that encourage high acts of racism. The impact of this increase in racism formed a resistance through a community called Hate is a Virus. This community moves by utilizing a network society approach due to limited physical activity. By using qualitative methods and library studies, this paper focuses on describing the efforts made by the Hate is a Virus community. The form of resistance from the community to advocate for Asian Americans is by collecting donations, campaigning through hashtags and educating through social media.